Service Quality Provided by Colleges in Chitwan and Its Impact on Student Satisfaction - Poudel, Shiva Prasad (Nepalese Journal of Management Research, 2021)
This study attempts to examine the relationship between service quality dimensions (tangibility, reliability, responsiveness, assurance and empathy) and students’ satisfaction. Furthermore, this study is also examining critical factors in service quality dimensions (tangibility, responsiveness, reliability, assurance and empathy) that contribute most to the satisfaction of the students. The study employed both purposive and stratified sampling technique by using a set of questionnaires that was distributed to 120 college students in three of the colleges (Balkumari College, Saptagandaki Campus and Birendra Multiple Campus) in Chitwan. However the study found that there is a positive significant relationship between service quality dimensions and students’ satisfaction. The study also found that Empathy has significant relationship with student’s satisfaction in the students’ perception of service quality rendered by their colleges. Finally the study concludes that assessing level of satisfaction and continuous improvements of the quality of services that colleges provide to their students will help management and other staff of these colleges to reach organizational success.